A life course perspective on the start of Black middle-class women's recreational running careers. Issue 4 (3rd July 2020) - Smith-Tran, Alicia
Abstract: This study is informed by two questions: How can studying the biographies of Black middle-class women illustrate how early life experiences shape adulthood health and leisure choices? More specifically, what life course processes affect one's ability and choice to become a recreational runner? Using life story data, I utilize two interrelated concepts from the life course perspective, cumulative processes and turning points, to highlight how both of these social processes affect decisions to running recreationally. For the women in the study whose running stories exemplify cumulative processes, their narratives focused on the continuation of middle-class health and leisure practices from childhood and adolescence. Other participants' narratives centered on poignant biographical moments related to health that served as key turning points that significantly altered participants' exercise trajectories in adulthood. This subset of women were oftentimes working class or poor as children. The findings of this study have implications for why it is important to take an intersectional, long-armed approach to understanding Black women's health and leisure during adulthood.